Analisis Kualitas Website SMA Negeri 2 Kota Jambi Menggunakan Metode Webqual 4.0 - Apriyani; Benni Purnama; Herry Mulyono (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2024)
SMA Negeri 2 Kota Jambi is a senior high school that uses the website as an information media, but there are still problems on the website, including when opening the website portal it is suspended, then there is no information about us in the sectioninformation about history, vision and mission, and there is also no information about holidays and semester exams. from these problems, a study was conducted to determine the relationship or correlation of each variable or all variables using the webqual 4.0 method with a total sample of 304 respondents and data processing using IBM Statistics SPSS software. The results of the study show that the quality of use has a significant effect on user satisfaction compared to the quality of interaction and the quality of information. it is suggested to the management of the SMA Negeri 2 Kota Jambi website to improve the quality of information by including information about history, vision and mission, information about holidays and semester exams and the website must be improved by providing an uptime serverand always respond to complaints or questions submitted by students through discussion forums.